Analisis Performa Algoritma Kompresi Data dalam Penyimpanan dan Transfer Data - Aruan, Meri Chrismes; Wanti Rahayu (LANCAH: Jurnal Inovasi dan Tren, 2023)
In the rapidly developing information era, efficiency in data storage and transfer becomes crucial. This research aims to analyze the performance of various data compression algorithms in the context of data storage and transfer. A literature review was conducted to understand the theoretical basis, types of compression algorithms, and factors influencing performance. The research methodology involves controlled experiments to measure compression ratios, compression and decompression speeds, as well as algorithm adaptability to data variations. The research results provide deep insight into the efficiency of each algorithm in various situations. The conclusion highlights the advantages and disadvantages of specific algorithms, providing practical recommendations for algorithm selection based on application needs.